On the reliability of self-reported health: Evidence from Albanian data☆ - Nicolas Vaillant; François-Charles Wolff (Springer, 2019)
This paper investigates the reliability of self-assessed measures of health using panel data collected in Albania by the World Bank in 2002, 2003 and 2004 through the Living Standard Measurement Study project. As the survey includes questions on a self-assessed measure of health and on more objective health problems, both types of information are combined with a view to understanding how respondents change their answers to the self-reported measures over time. Estimates from random effects ordered Probit models show that differences in self-reported subjective health between individuals are much more marked than those over time, suggesting a strong state dependence in subjective health status. The empirical analysis also reveals respondent consistency, from both a subjective and an objective viewpoint. Self-reported health is much more influenced by permanent shocks than by more transitory illness or injury.